Tinjauan Yuridis Bukti Ilmiah Penyelesaian Perkara Kebakaran Hutan dalam Persfektif Hukum Lingkungan - Octa Vera; Serlika Aprita; Kurniati Kurniati (Wajah Hukum, 2022)
Exploration of the natural world is becoming more and more popular since it is seen as being for human benefit. One illustration of how certain reckless elements inflict damage is forest fires. The Kalimantan and Sumatra forest fires had a significant negative impact on ecosystems, society, and the economy. In this journal, the problem of forest fires will be studied from the perspective of environmental ethics theory, namely Anthropocentrism and Biocentrism, where the two views contradict each other related to exploitation that should not be carried out by humans as kholifatul fil Ard. This journal uses the library method using scientific article journals and theses. From the second paradigm on environmental ethics, this study will produce the right perspective in this era regarding the relationship between humans and nature, so that the perspective of society in general can change and can take advantage of this nature according to its portion. Because in the Qur'an it has been explained that some of the damage that exists on earth comes from humans.